Perancangan User Experience Aplikasi Pemesanan Bengkel berbasis Mobile menggunakan Metode Design Thinking. (Studi Kasus Bengkel Harto Motors) - Mayshal Aldo Krisnanda; Riswan Septriayadi Sianturi; Agi Putra Kharisma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The increase in private vehicles is directly proportional to the increase in the number of maintenance and repairs of private vehicles. Harto Motors, one of the maintenance and repair workshops in Malang City, has a high enough demand for workshop services. However, reservations at Harto Motors are still manual. This manual system is often difficult for both the workshop and the customer. This study designed a mobile application user experience to assist and provide convenience in making reservations. The method used in this research is Design thinking because this method focuses on potential users and their nature of interacting with users in finding solutions. For validation, this study uses usability testing on 10 respondents who get an effectiveness aspect value of 91.5%, an efficiency aspect of 0.10 goals/sec, and a satisfaction aspect of 83.5 which includes grade B in the excellent category and also in the acceptable category. Furthermore, the test was also carried out using a user experience questionnaire (UEQ) which was tested on 20 respondents and got the results of the attractiveness aspect of 2.30, the results of the perspicuity aspect of 2.39, the results of the efficiency aspect of 2.44, the results of the dependability aspect of 2.08, the result from the stimulation aspect is 2.09, and the result from the novelty aspect is 1.99. The results of usability testing and UEQ are used as the basis for researchers to make interface improvements according to the feedback given by the respondents.